Aspects of Inner-Korean relations examined from a German viewpoint - Sven Horak (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2010)
This paper series takes a look at several aspects of inner-Korean relations, primarily in the area of international relations and economic cooperation, from a German viewpoint. In fact, the complexity of the respective subjects touched in this frame would require a deeper and more comprehensive analysis than developed here. The underlying idea is to stimulate further thought in several areas of pre- and post unification aspects by deriving inspiration from Germany's historical experience. The pre-unification phase and, specifically, the post-unification experience in Germany are of value to both Koreas. Further joint research is recommended on historical and contemporary aspects of German reunification that is relevant and suitable to Korea.
Keywords: O; F59; P2; P35; 330; international relations; policy; economic development; Korea; Germany; Internationale Beziehungen; Entwicklungskooperation; Korea; Nordkorea; Südkorea; Nationale Einheit; Deutschland